﻿Roma e Montecassino : gli affreschi della chiesa inferiore di S. Crisogono - Brenk, Beat (RACAR : Revue d'art canadienne / Canadian Art Review, 1985)
Attention is focused on mediaeval frescoes in the lower church of San Crisogono (surviving in part), which have not systematically been examined before. Questions such as the probable date of execution, the identity of the commissioner and the significance of the decoration are asked and answered. The usual dating of the decoration to the 10th century is, on the basis of new stylistic and iconographic evidence, shifted to the 11th century and more specifically after 1041 when the legend of Saint Benedict received visual expression in the Abbey of Montecassino. This decorative cycle appears to be a key in unlocking the dating of the cycle in S. Crisogono, in providing an iconographic model for the depiction of the various scenes, and quite possible in offering not only a stylistic reference point but also in providing the patron of the Roman frescoes. It is proposed that the patron was the abate Federico da Montecassino, who was also cardinal of S. Crisogono and for a short time before his death in 1057, Pope Stefanius ix. If this suggestion is appropriate, then new information can be obtained from the cycle regarding 11th-century mural decoration and the importance of S. Crisogono in the development of this tradition.